How does proactive motivation affect job crafting in Mamuju hospitals? - Eka Fatmawati; Andi Indahwaty Sidin; Lalu Muhammad Saleh (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Information about proactive motivation (PM) is important to hospital manager to predict the Job crafting (JC) behavior of hospital staff. High JC may lead to employee satisfaction and employee engagement at organization. Furthermore, it can improve staff performance and support the achievement of organizational goals. Individuals with proactive personalities are also most likely to change their work environment proactively. Motivation proactive can be generated by self efficacy and motivation internal. The purpose of this research was to analyze the ability of PM to stimulate JC behavior of hospital staff. This study was a cross sectional study. One hundred fifty five (155) staff was selected from 641 population in three (3) hospitals in Mamuju Regency. Data was analyzed by linear regression analysis. The research shows that 89 % of sample had good PM and based on profession, more medical doctors had good PM than nurses. The bivariate analysis of PM and JC found that the p. value was 0,000 less than ⍶-value 0,05. It means that statistically, PM influenced the JC. Proactive motivation affects job crafting by 16.2%. When the hospital staff have high PM then the JC can be generated. The hospital manager should create working environment to foster PM among staff.